SIGNIFICADOS DA LEITURA PARA O JOVEM NIETZSCHE (Revista de História Regional, 2007)
On the basis of some indications we tried to mount a picture of some representations that the young Nietzsche made on the act of readind and writing. It is observed that such representations, initially marked by very personal objectives, acquired a political and contestatory meaning regarding the forms of reading taught in Germany during the second half of the 19th Century.